REGULASI DIRI, PEER SUPPORT, DAN BURNOUT PADA MAHASISWA DIFABEL - Arthur Huwae; Maria Prima Novita (Psychocentrum Review, 2022)
Digital-based learning problem, particularly during COVID-19 pandemic, has given both serious obstacles and risks to the student with disability. Under a rather limited self-sustaining capacity, often it inhibits each learning dynamic that are being held. This challenge will certainly affect the mental and physical health of the students. Hence, the effort requires adequate self-provision and environmental roles to facilitate the student with disability to surpass the obstacles. Therefore, this study aims to understand the correlation between self-regulation and peer support to burnout in undergraduate student with disability. This study uses quantitative design with multiple correlation approach. The research participants were 41 students selected using snowball sampling technique. The measurement scale consists of self-regulation scale, peer support scale, and burnout scale. The result of the study shows that there is a similar correlation between self-regulation, peer support and burnout. Each independent variables has significant negative relationship with the student's burnout. Low levels of burnout illustrate how students with disabilities are able to improve their self-regulation skills and able to seek and acquire appropriate support from college friends, to address any difficulties in the educational process.